2020
DOI: 10.1007/s42247-020-00096-z
|View full text |Cite
|
Sign up to set email alerts
|

Electron irradiation induced aging effects on radiative recombination properties of quadruple cation organic-inorganic perovskite layers

Abstract: Understanding the role of defects in hybrid organic inorganic perovskites (HOIPs) is critically important to engineer the stability and performance of photovoltaic devices based on HOIPs. Recent reports on multi-cation compositions of general formula (A 1 ,A 2 ,A 3 ,A 4)Pb(X 1 ,X 2 ,X 3) 3 , where the A sites can be occupied by a distribution of 2-4 metallic/ organic cations and X sites with halide anions have shown stabilization effects against the well-known methyl ammonium lead triiodide (CH 3 NH 3 PbI 3), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 55 publications
(118 reference statements)
0
3
0
Order By: Relevance
“…[144,164] In study of GA 0.015 Cs 0.046 MA 0.152 FA 0.787 Pb(I 0.815 Br 0.185 ) 3 , the defects can be controlled by electron irradiation, which further influence the photoelectric properties and stability. [165] A-X Sites Doping in LD POIHPs: The 2D-3D mixed perovskite with A and X sites doping is found. [145,166,167] The n-propylammonium iodide (PAI) can be added into FA 0.79 MA 0.16 Cs 0.05 PbI 2.5 Br 0.5 , which forms 2D-3D mixed (PA) 2x FA 0.79 MA 0.16 Cs 0.05 Pb 1+x I 2.5+4x Br 0.5 system, where the Cs + can suppress photoinactive δ-phase of FAPbI 3 while PA promotes the energy level match (Figure 7c), reduces recombination and trap states in perovskite, and forms a 2D (PA) 2 PbI 4 covering layer with RPP crystal structure that changes wettability of the film surface to become hydrophobic against humid environment.…”
Section: A-x Sites Dopingmentioning
confidence: 90%
See 1 more Smart Citation
“…[144,164] In study of GA 0.015 Cs 0.046 MA 0.152 FA 0.787 Pb(I 0.815 Br 0.185 ) 3 , the defects can be controlled by electron irradiation, which further influence the photoelectric properties and stability. [165] A-X Sites Doping in LD POIHPs: The 2D-3D mixed perovskite with A and X sites doping is found. [145,166,167] The n-propylammonium iodide (PAI) can be added into FA 0.79 MA 0.16 Cs 0.05 PbI 2.5 Br 0.5 , which forms 2D-3D mixed (PA) 2x FA 0.79 MA 0.16 Cs 0.05 Pb 1+x I 2.5+4x Br 0.5 system, where the Cs + can suppress photoinactive δ-phase of FAPbI 3 while PA promotes the energy level match (Figure 7c), reduces recombination and trap states in perovskite, and forms a 2D (PA) 2 PbI 4 covering layer with RPP crystal structure that changes wettability of the film surface to become hydrophobic against humid environment.…”
Section: A-x Sites Dopingmentioning
confidence: 90%
“…[ 144,164 ] In study of GA 0.015 Cs 0.046 MA 0.152 FA 0.787 Pb(I 0.815 Br 0.185 ) 3 , the defects can be controlled by electron irradiation, which further influence the photoelectric properties and stability. [ 165 ]…”
Section: Doping Strategiesmentioning
confidence: 99%
“…Several experimental and theoretical studies demonstrated that the catalytic activity of perovskite oxides can be intrinsically modulated through the inductive alteration of oxygen nonstoichiometry to generate oxygen-deficient structures for a myriad of applications [35][36][37][38][39]. Table 1 summarizes various electrocatalysts made of oxygen-defected perovskite oxides that were reported in the literature for OER.…”
Section: Introductionmentioning
confidence: 99%